B1 Sequence-based real-time Quantitative PCR: A sensitive method for direct measurement of mouse plasma DNA levels after gamma irradiation - Zhang, Hengshan (2009)
PURPOSE: Current biodosimetric techniques for determining radiation exposure have inherent delays, and quantitation and interpretation limitations. We have identified a new technique with the advantage of directly measuring circulating DNA by amplifying inter-B1 regions in the mouse genome, providing a sensitive method for quantitating plasma DNA. METHODS AND MATERIALS: Real-time quantitative PCR was used to detect levels of DNA by amplifying inter-B1 genomic DNA in plasma samples collected at 0-48 hrs from mice receiving 0-10 Gy total- or partial-body irradiation [(137)Cs γ-ray source at ≈1.86 Gy/min (homogeneity: ±6.5%)]. RESULTS: The correlation coefficient between DNA levels and the threshold cycle value (C(T)) was 0.996, and the average recoveries of DNA in the assay were 87%. This assay revealed that when BALB/c mice were exposed to 10 Gy TBI, plasma DNA levels gradually increased beginning at 3 hours after irradiation, peaked at 9 hours, and returned to baseline within 48 hours. Increased plasma DNA levels were also detected following upper-torso or lower-torso partial-body irradiation; however, TBI approximately doubled those plasma DNA levels at the same radiation dose. This technique therefore reflects total body cell damage. The advantages of this assay are that DNA extraction is not required, the assay is highly sensitive (0.002 ng), and results can be obtained within 2.5 hours after collection of plasma samples. CONCLUSIONS: A radiation dose-dependent increase of plasma DNA was observed in the dose range from 2—10 Gy, suggesting that plasma DNA may be a useful radiation biomarker and adjunct to existing cell-based assays.